(untitled) - غفار, سفین رفعت; عبداللە, هەرێم احمد; رسول, ڤان سامان حاجی (Sulaimani Journal for Humanities, 2021)
The current study is an empirical attempt to measure the profitability of commercial banks in developing countries. It deals with aspects of understanding the impact of a number of firm-specific factors such as liquidity, debt leverage, retained earnings, bank size, growth rate and age of the bank on the profitability of commercial banks in Iraq for the period between 2009 and 2018. The sample study includes a number of commercial banks listed on the Iraq Stock Exchange. Data were collected from banks for the above period and analysed by using the multiple linear regression model and Brinson correlation coefficient using EVIEWS program. The results of the empirical analysis show that liquidity ratio, leverage ratio, retained earnings ratio, bank size and growth rate have a positive impact on the profitability of Iraqi commercial banks, with a negative impact from the age of the bank. The study recommends the necessity of conducting more in-depth studies in the field of profitability determinants, to include other non-financial sectors that have a distinctive position in the economic sectors in the Iraq Stock Exchange, to find out the extent of the variation in the determinants of profitability in the different sectors.
Keywords: profitability measurement; profitability determinants; commercial banks; internal factors; Iraq